KORELASI DIAMETER TAJUK AERIAL DAN DIAMETER BATANG SETINGGI DADA (130 CM) BERBASIS CITRA DRONE DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) MANDIANGIN KALIMANTAN SELATAN - Hanifa Auliya; Mufidah Asy'ari; Ahmad Jauhari (Jurnal Sylva Scienteae, 2020)
Many developed remote sensing to estimate the potential of the forest, one of them using drones, but important parameters such as stem diameter as high. The aim of this study was to determine the correlation model of aerial canopy diameter with chest diameter at the drone based tree. This research was conducted from February to April 2019 in Kawasan Hutan dengan Tujuan Khusus (KHDTK) Mandiangin, Lambung Mangkurat University, South Kalimantan. Air canopy diameter measurements were carried out on drone images in three density classes identified from the NDVI analysis, while breast diameter at breast height was carried out on land.  The results of this study are the formation of a positive linear correlation model between stem diameter and aerial canopy diameter with the equation y꞊ 7.0627x - 6.4252 with a coefficient of determination (R2) = 0.6984 and a correlation coefficient (r) of 0.83. This shows that diameter at breast height affects the aerial canopy diameter of 83%